Effect of Ethanol Extract of Chayote (Sechiumedule.Jacq.Swartz) on the Activity of Glutathione Peroxide (GPx) in House Mice (Musmusculus L) Strain DD Webster Hyperglycemia Induced by Streptozotocin (STZ) - Siahaan, Jekson Martiar; Harahap, Urip; Loesnihari, Ricke (Indonesian Journal of Medicine, 2016)
Background: Streptozotocin can cause hyperglycemia in guinea pig through the mechanism of oxidative stress which damages pancreatic b cells. Ethanol extract of chayote can decrease oxidative stress.  This study aimed to determine the effect of Ethanol Extract of Chayote ((EEBLS) Ekstrak Etanol Buah Labu Siam) on decreasing blood sugar content and increasing the activity of glutathione peroxide enzyme. Subjects and Method: This was an experimental study. The samples were using random sampling technique. The control group was using male white mice (Musmusculus L.) Strain DD Webster which randomized into four groups: negative control group, positive control group, group which got EEBLS of 100 mg/kgBB, and group which got EEBLS of 200 mg/kgBB.Results: The result of the research showed that there was significant decrease in blood sugar, compared with the control group. There was insignificant decrease in the activity of glutathione peroxide enzyme, compared with the control group.Conclusion: The conclusion of the research was that EEBLS of 200 mg/kgBB decreased blood sugar content of mice significantly, but there was no significant change in the activity of glutathione peroxide enzyme when EEBLS was given to the mice.   Keywords: streptozotocin, oxidative stress, antioxidant, flavonoidCorrespondence: Jekson Martiar Siahaan. Biomedical Science, Faculty of Medicine, North Sumatera University.Indonesian Journal of Medicine (2016), 1(1): 44-49https://doi.org/10.26911/theijmed.2016.01.01.06